Digitising - Time Estimation Using A Linear Regression Model - Said, Mohamad Nor; Desa, Ghazali (Fakulti Ukur dan Harta Tanah, 1993)
From data perspective, GIS can be regarded as having four subsystems namely data input, data storage and management, data manipulation and analysis and data output. Focusing on data input, manual digitizing has become the commonest practice but there is no standard way of quantitatively estimating the consumed time. This paper reports the results of an experiment to relate digitizing time to the total polygon perimeter contained in a map. A linear model was proposed and a linear regression technique was applied to test the model and to investigate the extent of its validity.